2000
DOI: 10.1242/jcs.113.11.2035
|View full text |Cite
|
Sign up to set email alerts
|

The LIM and SH3 domain-containing protein, lasp-1, may link the cAMP signaling pathway with dynamic membrane restructuring activities in ion transporting epithelia

Abstract: Lasp-1 is a unique LIM and src homology 3 (SH3) domain-containing protein that was initially identified as a 40 kDa cAMP-dependent phosphoprotein in the HCl-secreting gastric parietal cell. Because cAMP is a potent stimulator of parietal cell acid secretion, we have hypothesized that changes in lasp-1 phosphorylation might be involved in the regulation of ion transport-related activities, perhaps by modulating interactions among cytoskeletal and/or vesicle-associated proteins. In this study, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(5 citation statements)
references
References 45 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Increased expression of miR-338-3p suppressed the tumorigenesis of PTC-1 cells in the xenograft mouse model [32]. In addition, miR-338-3p was also reported to suppress cell mobility by downregulating phosphatidylinositol-3,4,5-trisphosphate-dependent Rac exchange factor 2 expression [32]. In the present study, the data indicated that circTIAM1 negatively regulated miR-338-3p activity to modulate cell proliferation and invasive ability.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Increased expression of miR-338-3p suppressed the tumorigenesis of PTC-1 cells in the xenograft mouse model [32]. In addition, miR-338-3p was also reported to suppress cell mobility by downregulating phosphatidylinositol-3,4,5-trisphosphate-dependent Rac exchange factor 2 expression [32]. In the present study, the data indicated that circTIAM1 negatively regulated miR-338-3p activity to modulate cell proliferation and invasive ability.…”
Section: Discussionmentioning
confidence: 50%
“…For example, miR-338-3p has been identified as a downstream effector of EGFR overexpression in breast cancer [31]. Increased expression of miR-338-3p suppressed the tumorigenesis of PTC-1 cells in the xenograft mouse model [32]. In addition, miR-338-3p was also reported to suppress cell mobility by downregulating phosphatidylinositol-3,4,5-trisphosphate-dependent Rac exchange factor 2 expression [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are (i) vitamin D receptor associated factor 1, also named ERC-55, belonging to the reticulocalbin family, a member of a new subfamily of the EFhand superfamily of Ca 2+ -binding proteins, specifically located in the ER. 34 The protein may contribute to cytoplasmatic signaling pathways potentially inducing apoptosis either indirectly through receptors initiating tyrosine phosphorylation or more directly via the Bcl-2 family system, the ceramide pathway, the death receptors (e.g., Fas) and the stress-activated protein kinase pathways (Jun N terminal kinase and p38); 35 (ii) An expressed sequence with features of a Rho GDP dissociation inhibitor and phosphotyrosine binding SH3 domains; Rho GTPases have been broadly discussed recently as antiinflammatory targets, in particular in neurodegeneration; 36 (iii) The third, Lasp-1, is involved in vesicle trafficking by actin and dynamin binding, has LIM and SH3 domains, 37 again pointing to specific HCA-induced events on the level of tyrosine phosphorylation. 38 The conspicuous occurrence of two members of dihydropyrimidinase-related protein (DHPRP) family prompted a more detailed MS approach: DHPRP, also called the collapsin response mediator protein, is implicated in the developmental process of the nervous system as well as in axonal growth and guidance.…”
Section: Discussionmentioning
confidence: 99%
“…SH3DCPs also control the molecular functions of enzymes, receptor activities, and transport processes [ 88 , 89 ]. SH3 domains are protein binding modules in enzymes like phospholipase Cγ [ 90 ].…”
Section: Dcps Belong To a Versatile Superfamilymentioning
confidence: 99%